Role of the cellular factor CTCF in the regulation of bovine leukemia virus latency and three-dimensional chromatin organization. Issue 6 (2nd March 2022) - Bellefroid, Maxime; Rodari, Anthony; Galais, Mathilde; Krijger, Peter H L; Tjalsma, Sjoerd J D; Nestola, Lorena; Plant, Estelle; Vos, Erica S M; Cristinelli, Sara; Van Driessche, Benoit; Vanhulle, Caroline; Ait-Ammar, Amina; et al.
Abstract: Bovine leukemia virus (BLV)-induced tumoral development is a multifactorial phenomenon that remains incompletely understood. Here, we highlight the critical role of the cellular CCCTC-binding factor (CTCF) both in the regulation of BLV transcriptional activities and in the deregulation of the three-dimensional (3D) chromatin architecture surrounding the BLV integration site. We demonstrated the in vivo recruitment of CTCF to three conserved CTCF binding motifs along the provirus. Next, we showed that CTCF localized to regions of transitions in the histone modifications profile along the BLV genome and that it is implicated in the repression of the 5′Long Terminal Repeat (LTR) promoter activity, thereby contributing to viral latency, while favoring the 3′LTR promoter activity. Finally, we demonstrated that BLV integration deregulated the host cellular 3D chromatin organization through the formation of viral/host chromatin loops. Altogether, our results highlight CTCF as a new critical effector of BLV transcriptional regulation and BLV-induced physiopathology.